A rare case of gastric linitis plastica revealed by isolated vertebral metastases in a young woman in a less developed country - ZOMALHETO, COSSI ZAVIER; KPOSSOU, ABOUDOU RAÏMI; AGBODANDE, KOUESSI ANTHELME; LARBRE, JP (My University, 2014)
We report a rare case of gastric linitis plastica revealed by vertebral metastases without another digestive dissemination. Case presentation: The Benin native woman was hospitalized in rheumatology for inflammatory back pain without another signs. Rx ray showed vertebra metastasis. In the etiologic research, gastroscopy showed an infiltrating lesion of the antral area, indicating gastric linitis which was confirmed by biopsy. Short and medium-term evolution was favourable, characterized by a complete disappearance of the pains and a good physical condition. Conclusion: Vertebral metastases can reveal digestive cancer, although human gut is not among the most bone metastatic cancers.
Keywords: Vertebral Metastasis; Gastric Linitis Plastica; Metastasis; Gastric Cancer